Research status and clinical management of hereditary colorectal cancer and gene disruption - Chen Yuanyuan; Yan Hongli (结直肠肛门外科)
The incidence and mortality of hereditary colorectal cancer have been increasing yearly, and a notable characteristic is a trend toward younger patients. With advancements in cancer treatment, assisted reproductive technology, and increasing patient demands for improved reproductive outcomes, determining how to help these patients achieve eugenics and fertility has become an important research direction in this field. Gene disruption can prevent the transmission of pathogenic genes from hereditary tumors to the next generation and has emerged as the optimal assisted reproductive strategy for these patients. This article provides an overview of the research status and gene disruption methods for hereditary colorectal cancer and proposes a comprehensive solution. Additionally, this solution may serve as a reference for gene disruption practices in other hereditary tumors.